Structural Investigation of Cerebellar Purkinje Cells of Rat Pups Whoose Mothers Were Exposed To Alcohol During Pregnancy and Lactation - Köksal, Mete; Ilgaz, Celal; Erdoğan, Deniz; Özoğul, Candan; Tong, Ebru K.; Kalender, Hakan (Fırat University, 2003)
Aim: In this study, it was intended to investigate the effects of alcohol on structures of fetal cerebellar Purkinje cells in semi thin sections. Materials and method: 12 adult female rats of Sprague-Dawley species were utilized. Control and experiment groups were formed. Rats were made pregnant. Rats in experiment group were administered liquid diet containing 6% alcohol. Cerebellums of infant rats were taken on 6th, 8th and 10th days after birth. Tissue samples were taken to routine electron microscopic procedure and then semi thin sections were examined. Results: When control and experiment groups were compared, it was determined that development in the experiment group was lesser than the control group. Conclusion: was determined that liquid diet containing 6% alcohol had toxic effects on Purkinje cells and caused structural alterations in these cells.

Amaç: Bu çalışmada alkolün fetal beyincik Purkinje hücreleri üzerine olan etkisinin yarı ince kesitte yapı düzeyinde incelenmesi amaçlandı. Gereç ve yöntem: Ergin Sprague-Dawley cinsi 12 dişi sıçan kullanıldı. Kontrol ve deney grupları oluşturuldu. Denekler gebe bırakıldı. Deney grubundaki sıçanlara % 6'lık alkol içeren sıvı diyet uygulandı. Doğumdan sonraki 6.,8. ve 10. günlerde yavruların beyincikleri alındı. Doku örneklerine rutin Elektron Mikroskobik takip yöntemleri uygulandı ve yarı ince kesitler incelendi. Bulgular: Deney ve kontrol grupları yapısal düzeyde karşılaştırıldığında, deney grubundaki gelişimin kontrol grubundan daha geri olduğu saptandı. Sonuç: %6'lık alkol içeren sıvı diyetin Purkinje hücrelerine toksik etkide bulunduğu ve bu hücrelerde yapısal düzeyde değişimlere yol açtığı belirlendi.
Gebelik Süresince ve Emzirme Evrelerinde Alkol Uygulanan Sıçan Yavrularının Beyinciklerindeki Purkinje Hücrelerinin Yapısal İncelenmesi